Compétences professionnelles et transfert des apprentissages des directions d’établissement en formation universitaire : une exploration franco-manitobaine - Archambault, Hélène Louise; Dumouchel, Gabriel (Canadian Journal of Education/Revue canadienne de l’éducation, 2021)
This research aims to identify the professional skills developed by students having completed the Master of Education program specializing in educational administration at Université de Saint-Boniface and to determine the conditions that facilitate or inhibit the transfer of learning. The research was conducted through a qualitative methodology centred on reflective journals and semi-structured interviews. The results indicate that the professional skill set developed by students within the educational administration program promotes change in their daily practices. Various conditions facilitating the transfer of learning are then identified to better explain this transformation. Keywords: educational administration training, professional skills, transfer of learning, educational administration, student academic success